National pride, trust in government and tax compliance: evidence from an environment of severe political instability - Mohamed Elmagrhi (Journal of Applied Accounting Research, 2025)
PurposeThis study examines whether national pride and trust in government can influence tax non-compliance among the Libyan self-employed taxpayers, drawing on insights from social identity and slippery slope theories.Design/methodology/approach This study utilised a quantitative research methodology by surveying 312 self-employed taxpayers in Libya. The collected data was then analysed using partial least squares structural equation modelling (PLS-SEM).FindingsThis study provides evidence that national pride and trust in government are positively and significantly linked to tax non-compliance behaviours among Libyan self-employed taxpayers. This finding is consistent with the expectations of social identity and slippery slope theories, indicating that lower levels of national pride and trust in government among Libyan self-employed taxpayers may contribute to their engagement in tax non-compliance behaviours. Research limitationsThis study uses data relating to Libyan self-employed taxpayer living in Tripoli, and hence the results of this study may not be generalisable to other regions of Libya.Practical implications The results of this study have important implications to governments, policymakers, tax authorities, and researchers. For example, our findings highlight possible opportunities for the Libyan government and tax authorities to increase tax compliance among self-employed taxpayers, where the findings may motivate these bodies to implement strategies that can enhance individuals’ sense of national pride and trust in government, and hence influence their tax compliance behaviours. Originality/value This study contributes and extends existing literatures by offering timely evidence on the extent to which national pride and trust in government can influence self-employed taxpayers’ tax compliance behaviours in an environment of severe political instability, where legal system is dysfunctional.